The effect of cetirizine on IFN-gamma and IL-10 production in children with allergic rhinitis - Uğuz, Ayşen; Sanlioğlu, Salih; Yüzbey, Selma; Coşkun, Mesut; Yeğin, Olcay (The Turkish Journal of Pediatrics, 2005)
Cetirizine, one of the most commonly used antihistamines for the treatment of allergic diseases, possesses some anti-inflammatory properties. Despite its common use, the effect of cetirizine on the production of cytokines from peripheral blood mononuclear cells (PBMCs) needs further clarification. The aim of this study was to investigate whether cetirizine changes interleukin (IL)-10, (IF)-gamma and IL-4 production from PBMCs in children with allergic rhinitis. Thirteen children with allergic rhinitis sensitized to house dust mite (HDM) were treated with cetirizine for four weeks. Blood samples were drawn just prior to the treatment, on the last day of the treatment and two weeks following the cessation of treatment The cytokine production from PBMCs was tested in the presence or absence of HDM allergen and measured by ELISA assay. An augmentation in IL-10 production was observed in PBMCs at the 4th week of cetirizine treatment (p